Explanatory asymmetries: laws of nature rehabilitated - Jansson, Lina (Journal of Philosophy, 2015)
The problem of explanatory non-symmetries provides the strongest reason to abandon the view that laws can figure in explanations without causal underpinnings. I argue that this problem can be overcome. The solution that I propose starts from noticing the importance of conditions of application when laws do explanatory work, and I go on to develop a notion of nomological (non-causal) dependence that can tackle the non-symmetry problem. The strategy is to show how a strong notion of counterfactual dependence as guaranteed by the laws is a plausible account of what we aim towards when we give law-based explanations. The aim of this project is not to deny that causal relations can do explanatory work but to restore laws of nature as capable of being explanatory even in the absence of any knowledge of causal underpinnings.